2007
DOI: 10.1073/pnas.0704299104
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of genes in cultured Drosophila neurons by RNA interference

Abstract: Cultures of neuroblasts that generate abundant neurons were established from Drosophila embryos to study silencing of genes by RNA interference (RNAi). Cultured cells expressed ELAV, a marker of neurons, Futsch, a marker of neurites, and Synapsin, Synaptobrevin, and Synaptogamin, proteins involved in neurotransmitter secretion. Conditions were found for efficient transfection of cells with siRNAs for ELAV or the insulin-like receptor, which resulted in marked decreases in neurons that express ELAV and Futsch. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Importantly, RNAi screens in Drosophila primary cultures can be carried out by a simple bathing method for dsRNA uptake. This is in contrast to the difficulties that have been reported with RNAi in mammalian cell lines and primary cells, which requires delivery of siRNAs into cells by chemical transfection or electroporation (Ovcharenko et al, 2005;Sharma and Nirenberg, 2007).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Importantly, RNAi screens in Drosophila primary cultures can be carried out by a simple bathing method for dsRNA uptake. This is in contrast to the difficulties that have been reported with RNAi in mammalian cell lines and primary cells, which requires delivery of siRNAs into cells by chemical transfection or electroporation (Ovcharenko et al, 2005;Sharma and Nirenberg, 2007).…”
Section: Discussionmentioning
confidence: 43%
“…As the different cell types can be tracked in primary cultures using a tissuespecific GFP, antibodies or other markers, primary-cell-based RNAi screens may be used to identify genes required in other differentiated cells as well [e.g. primary neurons (K. Sepp and N.P., unpublished) (Sharma and Nirenberg, 2007)]. Importantly, RNAi screens in Drosophila primary cultures can be carried out by a simple bathing method for dsRNA uptake.…”
Section: Discussionmentioning
confidence: 99%
“…RNA interference (RNAi) using double-stranded RNA (dsRNA) is a remarkably effective tool for suppressing specific gene expression in Drosophila cells (Goshima and Vale, 2003; Rogers et al, 2003; Sharma and Nirenberg, 2007). However neurons are generally thought to be less amenable to RNAi than other cell types.…”
Section: Resultsmentioning
confidence: 99%
“…His contributions to neuroscience were profound, and included the development and utilization of cell lines in neuroscience (Nelson et al 1976(Nelson et al , 1969Nirenberg 1978;Nirenberg et al 1983); the neuroblastoma and hybrid lines and the PC-12 cells developed by Lloyd Greene in Marshall's lab have been used in thousands of studies. He and his colleagues provided an useful cellular model of opiate addiction (Sharma et al 1975(Sharma et al , 1977 and have identified a number of novel genes that are important for nervous system development (Koizumi et al 2007;Sharma and Nirenberg 2007). They have identified new homeodomain genes (Kim and Nirenberg 1989;Rovescalli et al 1996).…”
mentioning
confidence: 97%